Community health workers: developing roles in public health dementia efforts in the United States - Johnson, Elma; Lewis, Mickal; Nordyke, Alexandra; Lee, Matthew; Roberts, Shelby; Gaugler, Joseph E.; Borson, Soo (Frontiers in Public Health, 2025)
Community Health Workers (CHWs) are a growing part of the healthcare workforce. Trusted in their communities, CHWs can provide essential health education and connection with culturally responsive health and support resources and programs. Despite their demonstrated effectiveness in improving outcomes in other chronic diseases such as diabetes, hypertension, HIV, and pediatric asthma, CHWs have been underutilized in dementia-related efforts. Properly equipped with education and skills, CHWs can fill important gaps throughout the dementia care continuum, strengthening public health efforts to support people with dementia and their families, especially in populations at higher risk such as African American, Latino and American Indian/Alaska Native groups. We outline key roles CHWs can play throughout the continuum of dementia care, improving brain health and reducing dementia risk at all life stages, such as improving early detection of cognitive impairment and helping caregivers navigate the daily challenges of dementia care in the community setting. Finally, we highlight key actions public health can lead to support the development of a dementia-capable workforce nationwide.